Regulation of alternative splicing by retrograde and light signals converges to control chloroplast proteins - Martín, Guiomar (Frontiers in Plant Science, 2023)
Retrograde signals sent by chloroplasts control transcription in the nucleus. These signals antagonistically converge with light signals to coordinate the expression of genes involved in chloroplast functioning and seedling development. Although significant advances have been made in understanding the molecular interplay between light and retrograde signals at the transcriptional level, little is known about their interconnection at the post-transcriptional level. By using different publicly available datasets, this study addresses the influence of retrograde signaling on alternative splicing and defines the molecular and biological functions of this regulation. These analyses revealed that alternative splicing mimics transcriptional responses triggered by retrograde signals at different levels. First, both molecular processes similarly depend on the chloroplast-localized pentatricopeptide-repeat protein GUN1 to modulate the nuclear transcriptome. Secondly, as described for transcriptional regulation, alternative splicing coupled with the non-sense mediated decay pathway effectively downregulates expression of chloroplast proteins in response to retrograde signals. Finally, light signals were found to antagonistically control retrograde signaling-regulated splicing isoforms, which consequently generates opposite splicing outcomes that likely contribute to the opposite roles these signals play in controlling chloroplast functioning and seedling development.